Identifying the Characteristic Delegation of Leadership: Study Literature Review - Fauzi Jaya Sakti, Reza; Sidjabat, Sonya; Sundari, Pipit; Subagio, Mochammad; Prasidi, Abi (Greenation International Journal of Tourism and Management, 2025)
The purpose of this literature study is to develop a hypothesis regarding the influence between variables that can be used for further research in the field of human resource management. The literature review article on the identification of leadership characteristics of delegates is a scientific literature article in the field of human resource management. The approach used in this literature review is descriptive qualitative. The data collection technique is to use a literature study or review relevant previous articles. The data used in this descriptive qualitative approach comes from previous research relevant to this study and is sourced from academic online media such as Thomson Reuters, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, each relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Leader Behavior affects Delegation Leadership; 2) Organizational Culture affects Delegation Leadership; 3) Trust affects Delegation Leadership; 4) Competence affects Delegation Leadership; and 5) Ability affects Delegation Leadership.